Modified ultrasonic time-of-flight diffraction testing with Barker code excitation for sizing inclined crack. (November 2018) - Han, Qingbang; Wang, Peng; Zheng, Hao
Abstract: Effectively sizing inclined cracks inside material is a difficult issue in ultrasonic non-destructive testing. To size the length, depth and orientation of inclined crack, a modified ultrasonic time-of-flight diffraction testing with double receivers (DR-TOFD) using Barker code excitation is proposed. The DR-TOFD technique is excited by Barker code, which has accurate time precision, and the diffraction wave of the crack tips is received by two receivers. The diffraction signals are compressed by matched filter to obtain desired detecting signals, which are used to estimate the length, depth and orientation of crack. Finite element method, which simulates wave propagation in specimen with a 6 mm crack with different inclination angles, is used to evaluate the detecting ability of the DR-TOFD with Barker code excitation. The simulation results show that the time precision of the proposed technique is up to 0.01 μs. Experiment is also performed to verify the detecting ability of DR-TOFD. The experiment results show that the proposed technique is able to expediently and accurately size inclined crack.